Prevalence of α-thalassaemia genotypes in pregnant women in northern Thailand - Pharephan S. (2017)
© 2016, Indian Council of Medical Research. All rights reserved. Background & objectives: Alpha-thalassaemias are genetic disorders with high prevalence in northern Thailand. However, common genotypes and current data on the prevalence of α-thalassaemias have not been reported in this region. Therefore, the objective of the present study was to determine the prevalence of α-thalassaemia genotypes in pregnant women in northern Thailand. Methods: Genomic DNA was extracted from blood samples of pregnant women who came to Maharaj Nakorn Chiang Mai University Hospital during July 2009 to 2010. The common deletion and point mutation genotypes of α-thalassaemia were evaluated by gap- polymerase chain reaction (PCR) and PCR with restriction fragment length polymorphism (RFLP). Results: Genotypes of 638 pregnant women were: 409 samples (64.11%) being normal subjects (αα/αα) and 229 samples (35.89%) with α-thalassaemias. These 229 samples could be classified into deletional HbH disease (-- SEA /-α 3.7 ) for 18 samples (2.82%); heterozygous α 0 -thalassaemia -- SEA type (-- SEA /αα)) for 78 (12.23%); heterozygous α + -thalassaemia - α 3.7 type (-α 3.7 /αα) for 99 (15.52%); homozygous α + -thalassaemia - α 3.7 type (-α 3.7 /- α 3.7 ) for five (0.78%); heterozygous α + -thalassaemia - α 4.2 type (-α 4.2 /αα) for two (0.31%); and heterozygous HbCS (α CS α/αα) for 27 (4.23%) cases. Interpretation & conclusions: The prevalence of α-thalassaemias in pregnant women in northern Thailand was high. This finding supports the implementation of the prevention and control of this common genetic disorder by screening for α-thalassaemia genotypes.